1995
DOI: 10.1007/bf01181553
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylated alpha-linked acidic dipeptidase is expressed by non-myelinating Schwann cells in the peripheral nervous system

Abstract: N-acetylated alpha-linked acidic dipeptidase is a membrane-bound brain peptidase which cleaves the neuropeptide N-acetyl-aspartyl-glutamate to N-acetyl-aspartate and glutamate. In the present study, we have determined the localization of N-acetylated alpha-linked acidic dipeptidase in the peripheral nervous system. Using enzyme assays and immunoblotting, we demonstrate that sciatic nerve, phrenic nerve, cervical dorsal root ganglion and superior cervical ganglion contain N-acetylated alpha-linked acidic dipept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 23 publications
2
55
0
Order By: Relevance
“…As shown in the autoradiograms in Figure 1, labeling of GCP II for all regions and conditions revealed two tightly spaced bands of approximately 85 and 100 kDa ('lower' and 'higher' band, respectively), as previously described by Berger et al (1995). GCP II is a class II membrane glycoprotein with a large extracellular domain that possesses several glycosylation consensus sites (Carter et al, 1996).…”
Section: Gcp II Expression In Corticolimbic Regionsmentioning
confidence: 87%
“…As shown in the autoradiograms in Figure 1, labeling of GCP II for all regions and conditions revealed two tightly spaced bands of approximately 85 and 100 kDa ('lower' and 'higher' band, respectively), as previously described by Berger et al (1995). GCP II is a class II membrane glycoprotein with a large extracellular domain that possesses several glycosylation consensus sites (Carter et al, 1996).…”
Section: Gcp II Expression In Corticolimbic Regionsmentioning
confidence: 87%
“…Later reports, however, revealed that low immunoreactivity levels to the 7E11-C5 antibody and its derivative CYT-356 (37,38) and/or mRNAs detected by RNase protection assays using PSMderived probes (41) were found in nonprostatic human tissues, including brain. A significant discrepancy nonetheless remains between the restricted pattern of expression of PSM in human tissues as detected by the aforementioned methods and the distribution of NAALADase in rat tissues including brain, kidney, sexual organs and peripheral nerves as determined by radioenzymatic assay (13,14,20,22), and immunodetection with anti-NAALADase antisera (20)(21)(22)42). The poor correspondences between the distribution of PSM and rat NAALADase may reflect the existence of multiple NAALADase isoforms, some of which are not reactive to the available detection reagents for human PSM.…”
Section: Resultsmentioning
confidence: 99%
“…The purified enzyme is a glycoprotein with a native apparent molecular mass of -94 kDa. Specific antisera raised against the purified glycoprotein demonstrate immunoreactivity that correlates with the distribution of NAALADase activity in rat brain, peripheral nerves, kidney, and sexual organs (20)(21)(22). The following report describes our use of these antisera to identify a human cell line cDNA that encodes a hydrolase activity with the substrate and pharmacologic properties of the NAALADase previously characterized in rat brain.…”
mentioning
confidence: 99%
“…GCP II is identical to prostate-specific membrane antigen and intestinal folate hydrolase (Serval et al, 1990;Slusher et al, 1990;Carter et al, 1996;Halsted et al, 1998). GCP II, a cell surface peptidase with its active site in the extracellular space, is expressed primarily by astrocytes in the brain (Berger et al, 1995b;Carter et al, 1996;Schwab, 1996, 1999). NAAG fulfills most of the criteria for a neurotransmitter or modulator (Kandel et al, 2000); however, its physiological actions are not well understood.…”
Section: Introductionmentioning
confidence: 99%